2022
DOI: 10.1155/2022/3239057
|View full text |Cite
|
Sign up to set email alerts
|

Role and Mechanism of the Renin-Angiotensin-Aldosterone System in the Onset and Development of Cardiorenal Syndrome

Abstract: Cardiorenal syndrome (CRS), a clinical syndrome involving multiple pathological mechanisms, exhibits high morbidity and mortality. According to the primary activity of the disease, CRS can be divided into cardiorenal syndrome (type I and type II), renal heart syndrome (type III and type IV), and secondary heart and kidney disease (type V). The renin-angiotensin-aldosterone system (RAAS) is an important humoral regulatory system of the body that exists widely in various tissues and organs. As a compensatory mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 84 publications
(113 reference statements)
0
16
0
Order By: Relevance
“…Aldosterone is the final effector of the RAAS, and the increased aldosterone contributes to cardiorenal damage, thus RAAS blockade has been considered to improve cardiovascular disease, hypertension, and diabetic CKD by controlling blood pressure and reducing vascular injury [ 29 ]. However, RAAS blockade in patients with perioperative AKI is controversial due to impaired autoregulation of glomerular and arteriolar pressure [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone is the final effector of the RAAS, and the increased aldosterone contributes to cardiorenal damage, thus RAAS blockade has been considered to improve cardiovascular disease, hypertension, and diabetic CKD by controlling blood pressure and reducing vascular injury [ 29 ]. However, RAAS blockade in patients with perioperative AKI is controversial due to impaired autoregulation of glomerular and arteriolar pressure [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…After 1 week of infusion of Ang II increase product extra culler matrix protein collagen and fibronectin with the continued rise CTGF and formation of fibrosis. After 2 weeks of infusion with Ang II increase level of TGF-β1 and CTGF by epithelial cells, mesangial cells and endothelial cells 49 . TGF-causes mesangial enlargement due to mesangial cell hypertrophy, proliferation (and eventually apoptosis), and the production of extracellular matrix (ECM).…”
Section: Groupsmentioning
confidence: 95%
“…This is likely an appropriate response as a meta-analysis synthesizing results from early COVID-19 studies showed hypertensive patients had 2.27- and 3.48-fold higher risk of severity and fatality due to COVID-19 infection, respectively [ 56 ]. ACE2 downregulation or inactivity poses a serious threat to human health as overactivation of the RAAS system is often a contributor to multi-organ failure [ 57 ].…”
Section: Disease Statesmentioning
confidence: 99%